Tingkat Pengetahuan Dan Sikap Ibu Menghadapi Masa Menopause - Cipto, Cipto; Siswoko, Siswoko; Saptaningrum, Epi (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
ABSTRACTBackground: Life is a process of continuous change from birth to death. One of the changes that are unavoidable and will face a woman is menopausal. Results of preliminary studies have been conducted in the village Kunduran showed that of 10 postmenopausal women (aged 45-55 years) is known that most do not know about menopause.Objectives: The general objective of the study was to determine the knowledge and attitude of mothers facing menopause. Interest in particular know the characteristics of respondents by education, employment, knowledge level and attitude of the mother in the face menopause.Methods: The study was a descriptive study using cross sectional method, the type of design that survey. Population is the mother menopause aged 40-45 years. Samples obtained through purposive sampling techniques, descriptive analysis with frequency destribusi.Results: The characteristics of respondents in terms of maternal education level premenopausal with basic education as much as 56 respondents (70%). While the work of the mother is a housewife 43 respondents (53.8%). The level of knowledge of mothers premenopausal good category 47 respondents (58.8%). Premenopausal mothers positive attitude as much as 47 respondents (58.8%). Keywords: Knowledge, Attitude, menopause